Italian versions of the Urogenital Distress Inventory-6 and Incontinence Impact Questionnaire-7: translation and validation in women with urinary incontinence. Issue 20 (25th September 2021) - Monticone, Marco; Frigau, Luca; Mola, Francesco; Rocca, Barbara; Giordano, Andrea; Foti, Calogero; Franchignoni, Franco
Abstract: Purpose: To culturally adapt and validate the Urogenital Distress Inventory-6 and Incontinence Impact Questionnaire-7 (short forms) for use in Italian-speaking women with urinary incontinence. Methods: We developed Italian versions of the two questionnaires through forward-backward translation, expert review and cognitive interviews. We then administered them to 100 women with urinary incontinence (mean age 58.02 ± 11.9 years) to assess the internal consistency (Cronbach's alpha), test–retest reliability (intraclass correlation coefficient), standard error of measurement, minimum detectable change, and construct validity by hypothesis testing. Results: No difficulties in acceptability emerged. Internal consistency was 0.61 for Urogenital Distress Inventory-6 and 0.88 for Incontinence Impact Questionnaire-7. Test–retest reliability was respectively 0.79 and 0.91. The minimum detectable change was respectively 22.9 and 18.1 points (on a 0–100 scale). Nine out of 10 a priori hypotheses regarding construct validity were confirmed. Conclusions: The Italian versions of the Urogenital Distress Inventory-6 and Incontinence Impact Questionnaire-7 showed reliability levels in line with the literature and good construct validity. Thus, we think that the present study extends the evidence for both questionnaires as useful tools for assessing women with urinary incontinence. Implications for rehabilitation: The Italian versions of the short forms of the Urogenital Distress Inventory and the Incontinence Impact Questionnaire have never been validated in Italian-speaking women with urinary incontinence. After translation and cross-cultural adaptation, the Italian versions of these two questionnaires showed reliability levels in line with the literature and good construct validity. The Urogenital Distress Inventory-6 produces a summary index of overall symptom distress, whereas the Incontinence Impact Questionnaire-7 is a unidimensional questionnaire measuring the adverse effects of urinary incontinence on health-related quality of life.